Changes of vegetation and its forces driving in the Aral Sea Basin of Central Asia - Zhang Xiangye; Liu Hailong; Chen Hui (E3S Web of Conferences, 2021)
Global change brings great uncertainty to the fragile ecological environment of arid area. In order to understand the driving role of climatic factors and socio-economic activity on changes, the distribution and change of vegetation in the Aral Sea basin were examined using data from remote sensing, population data sets from 2000 to 2015, transfer matrix, and the centre of gravity model. The salient results of the analysis were as follows. (1) Although the index increased slightly in the past 20 years overall, it fluctuated greatly over that time. From 2000 to 2015, the NDVI decreased in approximately 62% of the area; increased in 24%; and remained unchanged in 14%. (2) From 2000 to 2015, the geographic centre of the area under forest land to the northeast, marking the advancement of urbanization upstream. The geographic centre of grassland moved to the west. (3) The overall impact of precipitation on vegetation was greater than that of temperature. Areas showing a strong correlation were mostly concentrated in forest land; the impact of precipitation on grasslands was weak. (4) The distribution of vegetation was adversely affected by the increase in population and in GDP. The present study is of particular significance to the restoration and reconstruction of the Aral Sea basin ecosystem.